RESTORATIVE JUSTICE SEBAGAI ALTERNATIF PENYELESAIAN PERKARA PIDANA - Tambun, Joel Christofel Hinsa; Rustamaji, Muhammad (Sebelas Maret University, 2023)
This study aims to find out how restorative justice as an alternative dispute resolution in Indonesia and the benefits obtained when compared to conventional criminal justice processes. The type of research used is normative legal research which is prescriptive and applied. This legal research approach uses a case approach. The legal materials used consist of primary legal materials and secondary legal materials. The legal material collection technique used is library research. The legal material analysis technique used in writing this paper is the syllogism method with deductive thinking patterns. Based on the results of research and discussion it can be seen that the settlement with restorative justice as an alternative settlement of criminal cases focuses on restoring the original conditions between victims, perpetrators and society. Besides that, restorative justice settlement is the answer to the accumulation of files in court.Keywords: alternative dispute resolution; crimes; restorative justice